A Scientometrics Analysis on Brain-Inspired Intelligence. (September 2020) - Liang, Jianghai; Yang, Xiao; Liu, Shulei; Wu, Ji
Abstract: In recent years, brain-inspired intelligence has attracted increasing attention from both academia and industry. Although there are several literature reviews of brain-inspired intelligence research, they appear to be a lack of systematic quantitative and visual investigation. The purpose of this paper is to make insights into certain characteristics of brain-inspired intelligence research, and consequently to reveal the global trends as well as support researchers to determine future research directions. The data were retrieved from Science Citation Index Expanded (SCI-E) of core databases in Web of Science (WoS) and the global patent database of incoPat. Based on the aforementioned data and the scientometric techniques, we show the general characteristics of R&D (R&D) output, identify the research hotspots and the knowledge structure of brain-inspired intelligence and evaluate the R&D capability of countries, institutions. Finally, we conclude that (1) China, the United States, UK, Germany and South Korea are the main R&D forces in brain-inspired intelligence domain. (2) The researchers focus mainly on brain-computer interface, neuromorphic device, neuromorphic computing, and brain operation mechanism, and the R&D forces concentrate on the directions of G06N, G06F, A61B, G06K, H01L. (3) Major countries/regions pay more attention on academic cooperation and exchanges in brain-inspired intelligence. (4) America is leading in the basic research of brain-inspired intelligence. (5) China still has a big gap with the European and American countries in terms of industrial application.